Information Policies of Information Societies in the Realm of Capitalistic Type of Economic Systems - Fenerci, Tülay (Information World, 2004)
The age of information society represents a new economic, social and political era where information and information technologies are among primary instruments of production. Actually the mentioned societal characteristics flourish in the capitalist economic system. Both the capitalist system in itself and information society offer opportunities and consist challenges especially for developing countries. In order to get benefit from opportunities and reduce risks, the information policies should be formulated rationally. However the information policies should not be asserted only as a problem of implementing infrastructure.